From dispersed to monopolized violence: expansion and consolidation of the Primeiro Comando da Capital’s Hegemony in São Paulo’s prisons - Dias, Camila Nunes (Crime, law and social change, 2016)
The present work aims to understand the process of expansion and consolidation of the organized criminal group the Primeiro Comando da Capital (PCC) in São Paulo’s prison system over the past 20 years, and the social configuration that has formed as a result of the PCCs monopolization of opportunities of power. To this end, the work of Norbert Elias is utilized to analyze empirical data collected from various sources. The article consists of two lines of analysis. First, the PCC phenomenon is approached from a macro-sociological point of view, focusing on the social, political and administrative problems that are directly or indirectly linked to the PCCs social development. Second, a figurational analysis is used to explore the social dynamics produced from this process. In comparison to the "pre-PCC" situation, it is shown that the new social configuration produced from the hegemony of the PCC consists of a complexity of interdependencies, including greater functional division and social integration. Given this intensification of mutual dependencies, the social controls on individual behavior have been expanded and centralized. Here, the structure and organization of the PCC, its political dynamics, and individual self-control are central issues. The article concludes by calling into question the view that the most significant effect of the PCCs consolidation has been social pacification of São Paulo’s prison system. Fragilities in the power of the PCC are explored, principally the precarious nature of the relationship between the PCC and state authorities, and the extent to which the PCC’s authority is imposed.